2016
DOI: 10.1590/1807-1929/agriambi.v20n3p223-229
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Hymenaea stigonocarpa as a function of the addition of residues in degraded soil

Abstract: A B S T R A C TIn areas where soil surface horizons were removed, the main edaphic problems are reduced amounts of organic matter and nutrients. Revegetation, especially with native species, has been indicated to recover these areas. Under this perspective, the present research has been developed to evaluate the contribution of organic and agro-industrial residues, as conditioners of soil fertility and their effects on initial growth of 'Jatobá-do-cerrado' seedlings. The treatments consisted of 4 agro-industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
2
1
1
Order By: Relevance
“…The seedlings of the Cerrado species called Hymenaea stigonocarpa Mart. responded positively to substrates that were rich in organic matter and nutrients (Mizobata et al, 2016), being different from the results observed for A. peregrina.…”
Section: -9contrasting
confidence: 98%
“…The seedlings of the Cerrado species called Hymenaea stigonocarpa Mart. responded positively to substrates that were rich in organic matter and nutrients (Mizobata et al, 2016), being different from the results observed for A. peregrina.…”
Section: -9contrasting
confidence: 98%
“…For instance, Mizobata et al (2016) observed an increase in the SDM in H. stilbocarpa plants when organic residue was added to the substrate. Amaral et al (2016) demonstrated that a substrate containing 50% plant compound provided higher RDM, SDM and TDM in plants of Leucaena leucocephala (Lam.)…”
Section: Resultsmentioning
confidence: 99%
“…The larger doses of combined manure and biochar (CM30% + BC30%) presented better results for average height, differing from the control with 9% increase in height (2.2 cm) [ 69 ]. Different doses of agro-industrial residues (ash) in Hymenaea stigonocarpa produced positive effects after 8 months, such as a linear increase of height, ultimately yielding approximately 24% compared to control [ 13 ].…”
Section: Discussionmentioning
confidence: 99%